Genre Originality of Impressionist Novel (Virginia Woolf “To the Lighthouse”) - Куницька, Ірина Валеріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
This article offers to emphasise a genre variety of XX century’s novel, in particular impressionism. Genre constants and elements of poetics are defined, an originality of this form is revealed. The paper demonstrates that impressionistic novel significantly differs from the symbolist-decadent one. The first difference is the psychological nature. A tragedy and an acute conflict of a decadent worldview are being smoothed by the displacement of image focus on the touch subjectivism. Subtlety, elegance and aesthetics perception describe a person related to a decadent and a symbolist, but in the same time outline a different set of problems and are grounds for a storyline of another person.